Implementasi Metode Pengajaran Islam pada Masa Khulafaur Rasyidin: Studi Komparatif dengan Pendidikan Islam Modern - Rahmani, Ahadiana Diana (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The koran and hadith are sources of islamic religious education. The dynamics of change and development of education are discussed iin this journal. Education after the prophet Muhammad SAW. The death of islamic education developed during the reign of Khulafaur Rasyidin. All caliphs felt comfortable, and various situations contributed to the educational system of the time. The results of the research show that the educational principles applied by the caliph Abu Bakr were almost the same as the educational principles applied during the time of the prophet and developed rapidly during the time of the islamic caliphs. Umar bin Khatab was followed by the caliph Usman bin Affan, but the policies and pedagogy used underwent major changes.